When we went Mad! [videorecording (DVD)] : the unauthorized story of Mad magazine - Bernstein, Alan (Director); Adams, Nate (Director); Smensgard, Jonas; West, Scott (Cinematographer); Warburton, Patrick; Maurer, Jude; Bernstein, Lily (Gravitas Ventures, 2025)
MAD Magazine redefined humor with fearless satire of politics and pop culture. Featuring icons like Quentin Tarantino, this doc celebrates its wild legacy, free speech and the "Usual Gang of Idiots" who helped shape comedy forever.